2021
DOI: 10.12681/mms.27099
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian dynamics, batch fecundity and spawning phenology of the lessepsian migrant Etrumeus golanii DiBattista, Randall & Bowen, 2012 (Clupeidae: Dussumieriinae)

Abstract: The Golani’s round herring Etrumeus golanii is an Erythraean small pelagic fish (lessepsian migrant) that entered into the Mediterranean Sea through the Suez Canal. It has expanded its distribution from the east to the western Mediterranean with well-established local populations. We investigated basic aspects of its reproductive biology off the island of Crete (eastern Mediterranean) using ovarian histology and analysis of oocyte size-frequency distributions. The species exhibited a protracted breeding period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…In sardine, the spawning batch was separated from the SG pool since mid-vitellogenesis. A similar pattern is also reported for two other clupeids (Etrumeus teres: Plaza et al 2007; Etrumeus golanii : Somarakis et al 2021) in which the advanced batch grows rapidly after spawning and shortly separates from the smaller oocytes. In horse mackerel and mackerel, this separation took place at various phases of final oocyte maturation (FOM).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In sardine, the spawning batch was separated from the SG pool since mid-vitellogenesis. A similar pattern is also reported for two other clupeids (Etrumeus teres: Plaza et al 2007; Etrumeus golanii : Somarakis et al 2021) in which the advanced batch grows rapidly after spawning and shortly separates from the smaller oocytes. In horse mackerel and mackerel, this separation took place at various phases of final oocyte maturation (FOM).…”
Section: Discussionsupporting
confidence: 83%
“…Accordingly, the link with spawning dynamics was investigated by evaluating various attributes of ovarian dynamics, including the oocyte size frequency distribution, the ratio of total to batch fecundity, the histological clustering of oocyte cohorts, and the recruitment pattern from primary growth to secondary growth, as expressed by the numerical ratio of early secondary growth oocytes (ESG)-on-late primary growth oocytes (LPG). These aspects were related to historic estimates of spawning interval which is a variable of paramount importance in biomass assessments of commercial fish stocks through egg production methods (Ganias 2013), especially the Daily Egg Production method (DEPM; Stratoudakis et al 2006;Somarakis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Schismenou et al [10] have also shown that in the European anchovy de novo vitellogenesis occurred in parallel with PG to SG recruitment, while Wallace and Selman [2] mentioned that in the daily spawner medaka fish (Oryzias latipes), during the recruitment of oocytes into maturation, a new clutch of oocytes was recruited into vitellogenesis. In Etrumeus golanii, Somarakis et al [16] found that the final maturation of the advanced batch triggered the recruitment of oocytes into the subsequent batch, and after ovulation they started rapidly to grow in size to form the new advanced batch, a pattern similar to the one described here.…”
Section: Discussionsupporting
confidence: 75%
“…All the GLM analyses were performed using backward stepwise selection and only significant terms (p < 0.05) were retained in the final models. All assumptions, i.e., normal distribution of errors and homogeneity of variance, were met [16,31,32]. When no significant model could be fitted, sample means were used.…”
Section: Oocyte Number Trendsmentioning
confidence: 99%
See 1 more Smart Citation